Fine Particles in Medicine and Pharmacy - Matijević, Egon.; Matijević, Egon. (Springer US : Imprint: Springer, 2012)
Pharmaceutical manufacture is very exacting – for example, drugs must be uniform in size, shape, efficacy, bioavailability, and safety. The presence of different polymorphs in drug production is a serious problem, since different polymorphs differ in bioavailability, solubility, dissolution rate, chemical and physical stability, melting point, color, filterability, density, and flow properties. Fine Particles in Medicine and Pharmacy discusses particle size, shape, and composition and how they determine the choice of polymorph of a drug.